Comparison of endoscopy and CT scan in diagnosing chronic rhinosinusitis without polyps - Safavi Naini, Ali; Mehrparvar, Golfam; Emami, Habib (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Definite diagnosis of Chronic rhinosinusitis (CRS) is challenging mostly because of overlapping symptoms with other disorders. Nowadays it is mostly dependent on cross sectional imaging. When considering the prevalence and cost burden of CRS, reducing the frequency of cross sectional imaging by replacing it with endoscopic evaluation could be a cost effective way if the endoscopic examination proved to be a suitable substitution. Aim: The aim of this study is to compare the endoscopy with CT scan- as gold standard method- in diagnosis of CRS without polyp and to find out how well the results of the two correlate with each other. Methods: Adult patients with symptom criteria compatible with EPOS 2020 entered the study. They were evaluated endoscopically, and then scored by Lund Mackay CT score. Cases with obvious polyps seen on rhinoscopy or endoscopic evaluation were not entered the study. Results: A total of 49 patients entered the study. Comparing endoscopic findings with CT scan showed the sensitivity of 69.70% and specificity of 50%. Cohen Kappa statistics of 0.191 was obtained. Positive and negative predictive value was 74.19% and 44.44% respectively. Of note, all 8 patients with Kennedy score of 4 showed positive CT results, and, all 4 cases with isolated sinusitis had negative endoscopic results. Pearson correlation coefficient was 0.63, which showed a significant positive correlation between Lund Kennedy and Lund Mackay scores. (p<0.05) Conclusion: Our observations lead us to a possible need for revision in presented endoscopic criteria to increase the diagnostic power of endoscopy in chronic rhinosinusitis sine nasal polyposis.